On The Diskcyclic Criterions - Abdulkareem, Rana; Jamil, Zeana Zaki (Iraqi Journal of Science, 2020)
The aim of this work is to give the new types for diskcyclic criterion. We also introduced the case if there is an equivalent relation between a diskcyclic operator and T that satisfies the diskcyclic criterion. Moreover, we discussed the condition that makes T, which satisfies the diskcyclic criterion, a diskcyclic operator